ШЕТ ТІЛІН ОҚЫТУДАҒЫ ӘДІСТЕМЕЛЕР МЕН КОММУНИКАТИВТІК БАҒЫТ - Керімова, Ж. (Journal of Oriental Studies, 2016)
В статье рассказывается о методиках преподавания иностранного языка, а также коммуникативном подходе и его особенностях. The article deals with foreign language teaching methods, also communicative approach and its characteristics.